Implementation biases in wildlife trade regulation foster unscientific and inequitable intervention strategies - Kolby, Jonathan E.; Goodman, Orion L. B. (Frontiers in Conservation Science, 2025)
International conservation initiatives such as international wildlife trade regulation are important for species conservation efforts, but many current implementation models lend themselves to an environment that promotes biased values and inequitable distribution of benefits and responsibilities. This Perspective article aims to highlight prevailing sentiments observed among the international conservation community that contribute to asymmetrical discourse, policy development, and enforcement. These biases can limit the positive biodiversity impacts of interventions, preventing them from accomplishing species or landscape conservation goals. They can also contribute to mistrust between stakeholders, therefore adversely affecting relationships that are crucial to maintaining biodiversity and ecosystem services. Additionally, interventions and policies can be shaped more by subjective judgments of value than by science. The regulation of foreign bushmeat in the United States and the discourse surrounding it demonstrates the presence of value judgments in conservation policy. It also demonstrates how these value judgments appear to supplant evidence-based policy development and promote a landscape of wildlife resource use where some species and usages are permitted and others are considered unacceptable. The ramifications of these inequities can be seen in protected area and species management strategies globally but are particularly prevalent in African and Asian regions, where militarization and shoot-to-kill policies are in place. We argue that fostering sustainable wildlife resource use is enormously complex and requires a scientific, evidence-based approach to develop and implement initiatives that are both fair and effective. These arguments are supported through the use of select quotations from notable public authorities.